Characteristics and Surgical Success of Patients Presenting for Repair of Genitourinary Fistula in VVF Center of a Tertiary Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): To carry out a prospective review of patients who had undergone surgical repair of genitourinary fistula to determine patients characteristics and to explore success of surgery in relation to aetilogy of fistula and attempt of surgery.Materials and Methods : This cross-sectional study was carried out in patients attending the Fistula centre in Dhaka Medical College and Hospital (DMCH) from April 27th to July25th, 2013. Out of 47 patients 27 were recruited for this study. Detailed history was taken about socio-demographic character, gestational age, duration of labour, mode of delivery, conduction of labour and foetal outcome. Causes of fistula, information about fistula repair and success rate were noted. Main outcome measures were successful repair and correlation of success with aetiology of fistula, attempt of surgery. Data were analyzed by SPSS package. A p value of